Experimental Study on Fe3O4 Nanoparticle-Assisted Microwave Enhancing Heavy Oil - Teng Lu; Faqiang Dang; Haitao Wang; Qingmin Zhao; Zhengxiao Xu (Geofluids)
Nanoparticle-assisted microwave heating of heavy oil has the advantages of fast temperature rise and high thermal efficiency. Compared with traditional heating methods, it can reduce viscosity in a shorter time. In addition, the heavy components in the heavy oil are cracked into light components at high temperatures (this high temperature cannot be reached by conventional heating methods). This process is irreversible and avoids the problem of viscosity recovery of heavy oil after the temperature is reduced. Through absorbing microwave heating experiments, study the effect of nanoparticles on the improvement of the ability of heavy oil to absorb waves and raise temperature; through the heavy oil upgrading experiment and the four-component analysis experiment, the effect of adding hydrogen donor to assist microwave on the viscosity reduction of heavy oil upgrading by nanoparticles was studied, and the problem of viscosity recovery was determined; Through the gravity drainage experiment, the mechanism of nanoparticle-assisted microwave to improve the recovery of heavy oil is studied, and the influence of water content, nanocatalyst, and microwave power on the production of drainage is analyzed. The results show that nanoparticles can improve the wave absorption and heating capacity of heavy oil, and adding 0.6 wt% of nanomagnetic iron oxide catalyst can increase the heating rate of heavy oil in microwave by 60.6%; nanoparticle-assisted microwave heating method can effectively upgrade heavy oil and reduce viscosity. The experimental conditions are 2 wt% tetralin mass concentration, 0.5 wt% nano-Fe3O4 particle mass concentration, microwave heating time 50-60 min, and microwave power 539 W. Under this experimental condition, the viscosity is reduced by 40%. This method has viscosity recovery problems, but final viscosity reduction effect is still very significant. Obtaining the mechanism of nanoparticle-assisted microwave to enhance oil recovery, one of which is that nanoparticles improve the wave absorption and heating capacity of heavy oil and increase the heating speed of heavy oil; the second is that the nanoparticles form local high temperature under the action of microwave, which catalyzes the hydrocracking reaction between the heavy components in the heavy oil and the hydrogen donor, upgrading and reducing the viscosity of the heavy oil, and accelerating the production of heavy oil.